2019
DOI: 10.14295/ras.v33i1.29225
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da descontinuidade estrutural na hidrogeoquímica do aquífero Barreiras no nordeste do Brasil

Abstract: O aquífero Barreiras no campo de poços de Boa Cica, localizado no município de Nísia Floresta/RN, é composto por rochas siliciclásticas com espessura média da ordem de 65 metros. Na área estudada se encontra sobreposto a um aquitardo Mesozóico carbonático. Ambas as unidades, localmente, são interceptadas por um sistema de falhas nas direções NE-SW e NW-SE. O objetivo do presente trabalho é o entendimento da interação entre a estruturação geológica da área e as variáveis hidrogeológicas e hidrogeoquímicas do aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The Barreiras Aquifer, the stratigraphical unit homonym, has as its low limit in the study area the top of the nonoutcropping carbonatic Mesozoic sequence, which was identified by drilling as being formed by sandy clay and clay sediments of calciferous composition and low hydrogeological potentiality (Lucena, 2005;Silva et al, 2014;Stein et al, 2019;Alves and Lucena, 2021). In terms of hydraulic condition, such source is predominantly unconfined as it is evident by the broad interaction with the surface drainage (the aquifer has natural discharges toward the drainages, besides regional flow toward the coastline), as well as by the results of the aquifer tests performed.…”
Section: Thementioning
confidence: 99%
“…The Barreiras Aquifer, the stratigraphical unit homonym, has as its low limit in the study area the top of the nonoutcropping carbonatic Mesozoic sequence, which was identified by drilling as being formed by sandy clay and clay sediments of calciferous composition and low hydrogeological potentiality (Lucena, 2005;Silva et al, 2014;Stein et al, 2019;Alves and Lucena, 2021). In terms of hydraulic condition, such source is predominantly unconfined as it is evident by the broad interaction with the surface drainage (the aquifer has natural discharges toward the drainages, besides regional flow toward the coastline), as well as by the results of the aquifer tests performed.…”
Section: Thementioning
confidence: 99%